Exposure to respirable coalmine dust and incidence of progressive massive fibrosis. Issue 10 (October 1987) - Hurley, J F; Alexander, W P; Hazledine, D J; Jacobsen, M; Maclaren, W M
Abstract : Data gathered since 1953 concerning more than 30, 000 coalminers while employed at 24 collieries in England, Scotland, and Wales have been used to study the incidence of progressive massive fibrosis (PMF) in working coalminers. Results refer to 52, 264 approximately five year intervals when the miners were at risk of an attack of PMF. One objective of the present study was to describe how the five year attack rate of PMF was related to miners' age, colliery, and simple pneumoconiosis category at the start of the periods at risk. The main objective was to estimate the relation between exposure to dust and incidence of PMF and to examine how this relation changes in the presence of coalworkers' simple pneumoconiosis (CWSP). Film readings, in some cases based on clinical assessments only, showed 462 attacks of PMF over the five year risk periods. The men concerned had experienced higher cumulative exposures to dust than their colleagues of similar age at the same collieries, a result found at 65 of the 68 age colliery groups where an attack had occurred. The association was highly significant statistically. Simple pneumoconiosis clearly predisposed to PMF, with five year attack rates of 13.9%, 12.5%, 4.4%, and 0.2% among men with categories 3, 2, 1, and 0 respectively at the start of the risk periods. Once simple pneumoconiosis category 1 or more had been attained, those with higher cumulative exposure to dust were not at greater risk of an attack of PMF than other men with the same CWSP category. Among most miners, those with category 0, however, the risks of an attack of PMF increased clearly with exposure. Risks of an attack were higher among older men irrespective of CWSP category. In addition, there were large colliery specific variations in incidence related to variations in the carbon content of the coal though not fully explained by them. It is concluded that cumulative exposure to respirable dust is the decisive central factor in the development of PMF. Its effect is primarily in causing simple pneumoconiosis category 1 or higher which predisposes to PMF, though the dust related incidence among men with category 0 is not negligible in view of the large numbers at risk. Continuation of the policy to minimise dust concentrations underground therefore seems the only secure strategy to limit, and eventually eliminate, PMF.